Pengaruh Jumlah Konsentrasi Larutan Garam Pada Proses Quenching Baja Karbon Sedang S45C - Yunaidi Yunaidi (Universitas Janabadra, 2016)
Quenching is heat treatment process to increase the hardness and strength of steel. Important factors in the quenching include design of the equipment, type of coolant, coolant concentration, bath temperature, and motion rate during cooling. There are several types of cooling media that can be used in the quenching including water and oil. This study discusses the influence of dissolved salt concentration as a coolant in the quenching of S45C steel. The concentration of salt solution made variation between 0% to 25% by volume solution of 10 liters each. Quenching starts from the heating of steel in the furnace up to the austenitizing temperature and held at that temperature for 30 minutes followed by rapid cooling. Salinity in quenching media greatly influence the value of tensile strength and the hardness of steel. The higher salinity will decrease tensile strength and ductility. The higher salinity can accelerate the cooling process, evidenced by the emergence of a growing martensitic structure and refined at the higher salinity. Steel hardness will increase with increasing salinity.